Clinical perspectives on post-cholecystectomy syndrome: a narrative review - Changjin Nam; Jun Suh Lee; Ji Su Kim; Tae Yoon Lee; Young Chul Yoon (Annals of Medicine)
Introduction Post-cholecystectomy syndrome (PCS) is a complex condition characterized by persistent or new symptoms following gallbladder removal, affecting up to 47% of patients. Despite being recognized since 1947, there is still no consensus on its etiology, diagnosis, and treatment.Areas covered This narrative review explores the multifactorial etiology of PCS, including biliary and extra-biliary factors, and its varied clinical manifestations. A systematic literature search was conducted using keywords like ‘etiology’, ‘clinical manifestations’, ‘diagnostic challenges’, and ‘management strategies’. The review covers traditional diagnostic methods, recent insights into pathophysiology, and current management approaches, such as dietary modifications, pharmacological treatments, and endoscopic interventions, with a focus on patient selection.Expert opinion PCS presents significant clinical challenges due to its diverse presentations and lack of standardized diagnostic and therapeutic protocols. Effective management starts with careful patient selection before cholecystectomy to prevent unnecessary surgeries and reduce postoperative complications. Future research should aim to refine diagnostic criteria and develop predictive models for identifying at-risk patients. Personalized management strategies incorporating genetic, biological, and clinical factors are essential for improving outcomes. An integrated, patient-centered approach is crucial for addressing PCS complexities and enhancing the quality of life for affected patients.